Sequencing and analysis of complete mitochondrial genome of Apodemus draco (Rodentia: Arvicolinae). (3rd July 2016) - Wei, Haixue; Jia, Qiang; Li, Fengjun; Liu, Yongcheng; Chen, Shunde; Yong, Bin
Abstract: The genus Apodemus are the most common small rodents in fields. They are also one of the best species for biogeographic study and understanding the environmental changes. In this study, the complete mitochondrial genome sequence of Apodemus draco is determined. The mitogenome is 16 220 bp in length and contains 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes and a control region, with a base composition of 35.1% A, 29.0% T, 23.8% C and 12.1% G. The nucleotide sequence data of 12 heavy-strand protein-coding genes of Apodemus draco and other 23 rodents were used for mitochondrial genome phylogenetic analyses. The monophyly of the genus Apodemus was well supported with sister to the genus Mus . Bayesian analysis also suggested that Apodemus draco was a sister to Apodemus latronum . The present study may facilitate further investigation of the molecular evolution and biogeographic study of the genus Apodemus .